The urgency of Sasak local wisdom-based character education for elementary school in East Lombok, Indonesia - Ahmad Tohri; Abdul Rasyad; Muhammad Sururuddin; Lalu Muhammad Istiqlal (Institute of Advanced Engineering and Science, 2022)
The study discussed the urgency of character education in East Lombok elementary schools based on Sasak ethnic local wisdom. This study used descriptive qualitative research methods to describe the phenomena of educational activities, learning, and curriculum implementation related to character education based on local wisdom of the Sasak ethnic group in East Lombok elementary schools. Data were collected by using interview techniques, group observation, and documentation. Data analysis was organized into some categories, describing it into units, synthesizing, arranging into patterns, interpreting, and making conclusions. The main problem faced in the implementation of character education in East Lombok elementary school is the absence of a character education model that is appropriate or methodologically adequate for learning process, it is individually developed continuously. The richness and diversity of Sasak culture with the values of local wisdom has potential to be integrated holistically into the curriculum both in co-curricular, intra-curricular and extra-curricular aspects, and even has the leverage to become the basis for character education. So that character education in East Lombok elementary schools based on Sasak ethnic local wisdom is very urgent to be implemented.